La utilización de las TICS para el desarrollo cognitivo de los niños y niñas del primer año de educación general básica de la Escuela Juan Montalvo y la Escuela 11 de Noviembre del cantón Arenillas periodo 2013-2014. - Buele Masa, Tania Beatriz (2013)
Attending the object of study of this research is planned the following problem: What influence does the use of ICT in the cognitive development of children in the first year of basic general education school Juan Montalvo and school 11 November, the canton Arenillas, academic year 2013-2014 ?.